The effect of animated folk-tale video on the students’ ability in writing narrative text - Andjar Wulandari (SELL (Scope of English Language Teaching, Linguistics, and Literature) Journal, 2021)
Writing is one of the English skills that is considered difficult for senior high school students, especially SMAN 1 Bangkalan. The researcher tried to find out the significant increase between folklore animation videos and the conventional method from pre-test to post-test using independent t-test. In this quasi-experimental research, the researcher tried to find out how far the effect of animated folklore videos on the ability to write narrative texts of class XI students of SMAN 1 Bangkalan. In conducting the research, the writer used a quasi-experimental study by collecting data through pre-test, double treatment, and post-test. The research topic consisted of 148 students for the population and was divided into XI E (16 males and 13 females) and XI B (16 males and 14 females). The data were statistically calculated using an independent t-test to find differences in performance between students taught using animated folklore videos and students taught using conventional methods. Then it was found that the significance level was 0.01 or 1% and the observed t value was higher than the critical t value (3.1 > 2.756), which means H_1 is accepted and H_0 is rejected. In conclusion, the use of Animated Folklore Video in teaching narrative writing is appropriate, and the researcher suggests that this media be applied in real-world classroom teaching.